1988
DOI: 10.1021/ja00233a028
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the construction of radialenes by the nickel-catalyzed cyclooligomerization of [3]cumulenes (butatrienes)

Abstract: The zero-valent nickel complexes, which are generated in situ from nickel(I1) complexes by reduction with zinc, have been found to catalyze the cyclooligomerization of butatrienes, 2,3-dihalo-1,3-butadienes, 1,4-dichloro-2-butyne, and 1,l-dibromoethylene to give the corresponding [4]-and [6]radialenes. The formation of the [4]-and (6lradialenes depends on the reaction conditions, especially on solvent, and each product of the reactions can be prepared selectively. This method provides access to the synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 2 publications
0
30
0
Order By: Relevance
“…Compound 6a was synthesized in 62% yield when the reaction was carried out on a 5 mmol scale, and the Ni(PPh 3 ) 2 Br 2 -PPh 3 -Zn catalytic system was used (entry 2). 17b, 21 The cycloheptadiene 6b was also isolated in good yield when the reaction of 1, 2b, and 5 was executed (entry 3). The reaction of 1, 2c, and 5 proceeded in moderate yield to afford 6c (entry 4).…”
Section: Nickel-catalyzed [3 + 2 + 2] Cocyclization Of Ethylmentioning
confidence: 99%
“…Compound 6a was synthesized in 62% yield when the reaction was carried out on a 5 mmol scale, and the Ni(PPh 3 ) 2 Br 2 -PPh 3 -Zn catalytic system was used (entry 2). 17b, 21 The cycloheptadiene 6b was also isolated in good yield when the reaction of 1, 2b, and 5 was executed (entry 3). The reaction of 1, 2c, and 5 proceeded in moderate yield to afford 6c (entry 4).…”
Section: Nickel-catalyzed [3 + 2 + 2] Cocyclization Of Ethylmentioning
confidence: 99%
“…These molecules possess an uninterrupted cyclic arrangement of exocyclic double bonds. [27,28] Of special interest are compounds based on [3]radialenes (see model 4 in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…3 Although the cyclooligomerizations of ethylenes, acetylenes, allenes and butatrienes have been widely investigated, 4 only few examples are known of cyclotrimerization of cumulenes. Early studies showed that allenes trimerize at 130-200 1C in benzene to give isomeric cyclic trimers, 5 and butatrienes afford [6]radialenes upon transition metal catalyzed cyclotrimerization. 6 However, no reports are known for the trimerization of hexapentaenes, except for the oxidative cyclotrimerization of hexapentaene-extended quinocumulene.…”
mentioning
confidence: 99%
“…Early studies showed that allenes trimerize at 130-200 1C in benzene to give isomeric cyclic trimers, 5 and butatrienes afford [6]radialenes upon transition metal catalyzed cyclotrimerization. 6 However, no reports are known for the trimerization of hexapentaenes, except for the oxidative cyclotrimerization of hexapentaene-extended quinocumulene. 7 In a broader sense, thermal reactions of higher cumulenes have been studied only in limited cases, presumably due to instability of these highly unsaturated compounds in atmospheric oxygen.…”
mentioning
confidence: 99%